The grammar of causation and interpersonal manipulation - Shibatani, Masayoshi (Typological studies in language, 2002)
This volume presents fifteen original papers dealing with various aspects of causative constructions ranging from morphology to semantics with emphasis on language data from Central and South America. Informed by a better understanding of how different constructions are positioned both synchronically (e.g., on a semantic map) and diachronically (e.g., through grammaticalization processes), the volume affords a comprehensive up-to-date perspective on the perennial issues in the grammar of causation such as the distribution of competing causative morphemes, the meaning distinctions among them, and the overall form-meaning correlation. Morphosyntactic interactions of causatives with other phenomena such as incorporation and applicativization receive focused attention as such basic issues as the semantic distinction between direct and indirect causation and the typology of causative constructions.